2005
DOI: 10.1164/rccm.200404-528oc
|View full text |Cite
|
Sign up to set email alerts
|

Hyperventilation with Cold versus Dry Air in 2- to 5-Year-Old Children with Asthma

Abstract: Responsiveness to CACh exceeded responsiveness to DACh, and CACh seemed to induce refractoriness in contrast to DACh, probably because of the additional stimulus from airway cooling. This finding suggests CACh as the preferred method of challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…In order to have a high sensitivity, a reduction of 10% in FEV 1 has been considered as the appropriate limit for indirect tests compared with 15%, which have traditionally been used for some of these tests (for mannitol 15%). It has been demonstrated in several studies that the sensitivity of inhaling cold dry air is greater than the response to dry air only (119)(120)(121)(122) including one recent study in preschool children (123), whereas only one study has reported the opposite (124). The potency of the eucapnic voluntary hyperpnoea protocol recommended by the IOC Medical Commission independent panel probably relates to the use of 6 min at a target ventilation of 85% maximum voluntary ventilation (112).…”
Section: Measurement Of Bhr By Other Indirect Stimulimentioning
confidence: 99%
“…In order to have a high sensitivity, a reduction of 10% in FEV 1 has been considered as the appropriate limit for indirect tests compared with 15%, which have traditionally been used for some of these tests (for mannitol 15%). It has been demonstrated in several studies that the sensitivity of inhaling cold dry air is greater than the response to dry air only (119)(120)(121)(122) including one recent study in preschool children (123), whereas only one study has reported the opposite (124). The potency of the eucapnic voluntary hyperpnoea protocol recommended by the IOC Medical Commission independent panel probably relates to the use of 6 min at a target ventilation of 85% maximum voluntary ventilation (112).…”
Section: Measurement Of Bhr By Other Indirect Stimulimentioning
confidence: 99%
“…Cold air hyperpnea provokes bronchoconstriction in asthmatic subjects (30), especially in children and young adults (31,32). The pathophysiological mechanism beyond this response has been a matter of considerable debate.…”
Section: Cold Air-provoked Short-term Responsesmentioning
confidence: 99%
“…Coldair hyperventilation challenge, for example, has been shown to be useful in discriminating between children with and without asthma [127] and to correlate well with nonspecific bronchial reactivity measured by methacholine inhalation challenge [128]. Larger epidemiological studies have also shown that crosscountry skiers, a group of individuals whose training and competition generates high minute ventilation in cold environments, have a higher incidence of asthma and asthma-like symptoms when compared to nonathletic controls [129,130].…”
Section: Air Temperaturementioning
confidence: 99%